Seeing Suppresses Haptic Pleasure While Perceiving Contemporary Art. (June 2020) - Szubielska, Magdalena; Niestorowicz, Ewa
To date, haptic aesthetic processing has been tested outside the field of real works of art. By providing the context of a contemporary art exhibition designed to be touched, we studied haptic pleasure towards artworks. In line with our hypothesis, seeing affected the evaluation of haptic pleasure which was higher in the blindfolded-tactile than visuo-tactile condition. Thus, seeing seems to impede the tactile processing of artworks.